2022
DOI: 10.1002/ehf2.14018
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive adrenomedullin for assessment of venous congestion in heart failure

Abstract: Aims Bioactive adrenomedullin (bio-ADM) is a vascular-derived peptide hormone that has emerged as a promising biomarker for assessment of congestion in decompensated heart failure (HF). We aimed to evaluate diagnostic and prognostic performance of bio-ADM for HF in comparison to amino-terminal pro-B-type natriuretic peptide (NT-proBNP), with decision thresholds derived from invasive haemodynamic and population-based studies. Methods and resultsNormal reference ranges for bio-ADM were derived from a community-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
2
0
1
Order By: Relevance
“…29,30 A recent study found that bioactive plasma ADM were associated with MRAP and PAWP measured by RHC, thus proposing it as a biomarker of systemic venous congestion in patients with HF. 32 This is in line with our results demonstrating that ADM levels in patients with advanced HF correlated with MRAP and NT-proBNP. Elevated ADM levels have been demonstrated to successfully predict disease severity and prognosis in chronic HF.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29,30 A recent study found that bioactive plasma ADM were associated with MRAP and PAWP measured by RHC, thus proposing it as a biomarker of systemic venous congestion in patients with HF. 32 This is in line with our results demonstrating that ADM levels in patients with advanced HF correlated with MRAP and NT-proBNP. Elevated ADM levels have been demonstrated to successfully predict disease severity and prognosis in chronic HF.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, some studies suggest that ADM could reduce hypertrophy, remodelling, and fibrosis of the myocardium 29,30 . A recent study found that bioactive plasma ADM were associated with MRAP and PAWP measured by RHC, thus proposing it as a biomarker of systemic venous congestion in patients with HF 32 . This is in line with our results demonstrating that ADM levels in patients with advanced HF correlated with MRAP and NT‐proBNP.…”
Section: Discussionsupporting
confidence: 91%
“…Biomarkers that support accurate congestion assessment are desperately needed because congestion is infamously hard to measure accurately with high observer variability [ 95 ]. Recent studies highlight the strong association of increasing bio-ADM with systemic congestion and adverse outcomes independent of NT-proBNP [ 96 ].…”
Section: Reviewmentioning
confidence: 99%
“…BioADM has been studied as a marker in the evaluation of venous congestion associated with heart failure and correlates very well with measures of systemic congestion and mortality in decompensated heart failure. ADM is released by endothelial and vascular smooth muscle cells in response to intravascular volume overload and plays a key role in maintaining endothelial barrier function, thereby regulating tissue volume and edema [ 74 ]. In fact, the role of biomarkers to evaluate pulmonary and systemic congestion and distinguish phenotypes has recently been highlighted [ 75 ].…”
Section: The Best Biomarkers In Intensive and Perioperative Carementioning
confidence: 99%